Exploring Trust Factors in Human-GenAI Product Prioritization - Andreas Harnindito; Sujud Ganda Saputra (MDP Student Conference, 2026)
Product managers increasingly used Generative Artificial Intelligence tools such as ChatGPT, Claude, and Gemini to support product prioritization decisions. However, the factors that shaped trust in these tools within prioritization contexts remained underexplored. This research study investigated how product managers developed trust in GenAI for prioritization through semi-structured interviews with nine participants from Indonesia, Sweden, and Estonia. The thematic analysis revealed four overarching themes related to trust in GenAI for product prioritization: conditional confidence in GenAI ability, trust-building with GenAI through verification practices, data privacy and transparency concerns, and ethical concerns in GenAI use. No participant fully trusted or fully abandoned GenAI, instead adopting a pattern of cautious engagement. The study highlighted the need for organizational governance, clear data policies, and training programs to support appropriate trust calibration in GenAI-assisted product prioritization.